Anaerobic transformation of tetrachloroethane, perchloroethylene, and their mixtures by mixed-cultures enriched from contaminated soils and sediments - Aulenta, F (Water science and technology : a journal of the International Association on Water Pollution Research, 2005)
The focus of this research was to investigate the anaerobic transformation of tetrachloroethane (TeCA), perchloroethylene (PCE), and their mixtures by mixed cultures enriched from contaminated soils or sediments. Batch transformation studies were conducted using TeCA (60 microM), PCE (60 microM), or TeCA + PCE (each added at 60 microM) as electron acceptor(s) and H2 + acetate (each added at 3 mM) or butyrate (3mM) as electron donor(s). A Dehalococcoides spp.-containing, sediment-enrichment dechlorinated PCE rapidly to ethene (ETH) but slowly and incompletely dechlorinated TeCA. Moreover, when present in mixture with PCE, TeCA disrupted the ability of Dehalococcoides to dechlorinate vinyl chloride. In contrast, the soil-enrichment culture was able to completely dechlorinate TeCA and PCE to ETH, both when added as single contaminants and when added as a mixture